2023
DOI: 10.21203/rs.3.rs-2522089/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dihydrotestosterone Induces Arterial Stiffening in Female Mice

Abstract: Background: Testosterone is the predominant sex hormone in men and is increased in women with polycystic ovarian syndrome. These patients also experience an increased risk for cardiovascular diseases including hypertension and arterial stiffness. Since our previous work shows an important role for the G protein-coupled estrogen receptor (GPER) in arterial stiffness, we hypothesized that other hormones including androgens may impact arterial stiffness in female mice via regulation of GPER. Methods: The impact o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…The majority of values in intact mice were below the lower limit of detection of 2 pg/mL, as previously reported. 35,38 Including these values at the lower limit, we found that average estradiol levels were 13.2±21.7 pg/ mL in intact 20-week-old mice and 2.6±1.1 pg/mL in intact 52-week-old mice (n=7 per group). Both ovariectomy and aging increased intracarotid PWV and aortic PWV to a similar extent (Figure 1A and 1B).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The majority of values in intact mice were below the lower limit of detection of 2 pg/mL, as previously reported. 35,38 Including these values at the lower limit, we found that average estradiol levels were 13.2±21.7 pg/ mL in intact 20-week-old mice and 2.6±1.1 pg/mL in intact 52-week-old mice (n=7 per group). Both ovariectomy and aging increased intracarotid PWV and aortic PWV to a similar extent (Figure 1A and 1B).…”
Section: Resultsmentioning
confidence: 89%
“…Verhoeff–Van Gieson stain was used to quantify elastin, Masson trichrome stain was used for collagen and smooth muscle, and Alcian blue stain was used for glycosaminoglycans, as previously described. 20,28,35 Analysis was performed using Adobe Photoshop (v.24.5.0). For each tissue section, the entire cross section was imaged, and the number of pixels stained with the selected color was counted and expressed as an area fraction (percent of pixels with positive staining within the tissue area).…”
Section: Methodsmentioning
confidence: 99%